Pengaruh Stress Kerja Dan Motivasi Kerja Terhadap Semangat Kerja Karyawan Produksi CV Seribu Kubah Tulungagung - Nindi Trias Anggita Putri; Edy Suwasono; Heru Sutapa (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
In a company paying attention to and nurturing employees is very important for the sustainability of a company, if employees experience work stress then this can hinder work. While work motivation also needs to be considered so that employee morale increases so that the results of the performance carried out can go well. The sampling technique in this study used a saturated sample with 40 employee respondents. From this study the variable Work Stress (X1) shows a significant value of Sig. 0.037, namely > 0.05 which states that job stress has a partial effect on employee morale. Work Motivation Variable (X2) shows a significant value of Sig. 0.000, namely > 0.05 which states that job stress has a partial effect on employee morale. Simultaneously there is the influence of work stress and work motivation variables on the work enthusiasm of production employees at CV Seribu Kubah Tulungagung with a significant F test result of 0.000 or > 0.05.